Amoxicillin for acute lower respiratory tract infection in primary care: subgroup analysis of potential high-risk groups. - Moore, M; Stuart, B; Coenen, S; Butler, C; Goossens, H; Verheij, T; Little, P (2014)
BACKGROUND: Antibiotics are of limited overall clinical benefit for uncomplicated lower respiratory tract infection (LRTI) but there is uncertainty about their effectiveness for patients with features associated with higher levels of antibiotic prescribing. AIM: To estimate the benefits and harms of antibiotics for acute LRTI among those producing coloured sputum, smokers, those with fever or prior comorbidities, and longer duration of prior illness. DESIGN AND SETTING: Secondary analysis of a randomised controlled trial of antibiotic placebo for acute LRTI in primary care. METHOD: Two thousand and sixty-one adults with acute LRTI, where pneumonia was not suspected clinically, were given amoxicillin or matching placebo. The duration of symptoms, rated moderately bad or worse (primary outcome), symptom severity on days 2-4 (0-6 scale), and the development of new or worsening symptoms were analysed in pre-specified subgroups of interest. Evidence of differential treatment effectiveness was assessed in prespecified subgroups by interaction terms. RESULTS: No subgroups were identified that were significantly more likely to benefit from antibiotics in terms of symptom duration or the development of new or worsening symptoms. Those with a history of significant comorbidities experienced a significantly greater reduction in symptom severity between days 2 and 4 (interaction term -0.28, P = 0.003; estimated effect of antibiotics among those with a past history -0.28 [95% confidence interval = -0.44 to -0.11], P = 0.001), equivalent to three people in 10 rating symptoms as a slight rather than a moderately bad problem. For subgroups not specified in advance antibiotics provided a modest reduction in symptom severity for non-smokers and for those with short prior illness duration (<7 days), and a modest reduction in symptom duration for those with short prior illness duration. CONCLUSION: There is no clear evidence of clinically meaningful benefit from antibiotics in the studied high-risk groups of patients presenting in general practice with uncomplicated LRTIs where prescribing is highest. Any possible benefit must be balanced against the side-effects and longer-term effects on antibiotic resistance.